On Fuzzy Fixed Points and an Application to Ordinary Fuzzy Differential Equations - Eskandar Ameer; Hassen Aydi; Muhammad Arshad (Journal of Function Spaces)
The aim of this paper is to obtain the common fuzz fixed points of α-fuzzy mappings satisfying generalized almost Y,Λ-contraction in complete metric spaces. Our results are extensions and improvements of the several well-known recent and classical results in literature. We give an example for supporting these results. As an application, we apply our obtained results to study the existence of a solution for a second order nonlinear boundary value problem.